Conflict management styles and job satisfaction: a study among Malaysian public universities academicians - Mohd Kassim, Muhammad Asyraf; Abdul Manaf, Arman Hadi; Abdullah, Muhammad Safizal; Osman, Abdullah; Salahudin, Shahrul Nizam (2019)
The present study aims to investigate the relationship between conflict management styles and job satisfaction among academic staff in Malaysian public universities. Self-administered questionnaires were distributed to 300 academicians of various fields at public universities in northern part of Malaysia. Subsequently, data were analyzed using Statistical Package for Social Sciences (SPSS) and Partial Least Squares - Structural Equation Modelling (PLS-SEM). The findings indicate that several conflict management styles such as integrating, obliging, and compromising were positively significant with job satisfaction. However, the dominating and avoiding styles of conflict management were found to be negatively related to job satisfaction. Thus, all of the five styles of conflict management were significantly related to job satisfaction. Several suggestion and recommendation were forwarded at the end of the report based on the findings of the present study.